Improving Geometry Problem Solving Abilities Through Spatial Reasoning-Based Problem Based Learning in Elementary Schools - Resi Ratna Suminar; Meiliasari; Nurjannah (Jurnal Elementaria Edukasia, 2024)
Problem-solving abilities are the core of mathematics learning, but in reality the problem-solving abilities of elementary school students in particular have not shown satisfactory results. The aim of this research is to improve the geometric problem-solving abilities of elementary school students in class VB at SD N Cimanggis 02 by using a Problem Based Learning model based on spatial reasoning. This research is Classroom Action Research which was carried out on 38 students in class VB SD N Cimanggis 02 as research subjects and involving the class VB teacher as a collaborator. Obtaining data through geometric problem-solving ability tests, interviews, field notes and documentation. Indicators of problem-solving ability in this research include understanding the problem, planning a solution, implementing the problem-solving plan and evaluating or checking again. This PTK was carried out in three cycles with four research procedures, namely the planning stage, implementation stage, observation stage and reflection stage. In this case, there was an increase in geometric problem-solving abilities of 66% in cycle I and increased to 70% in cycle II and increased to 80% in cycle III. These results illustrate that Problem Based Learning based on spatial reasoning can improve the geometric problem-solving abilities of class VB students at SD N Cimanggis 02. Keywords: Problem-Solving Ability; Problem Based Learning; Spatial Reasoning